An efficient architecture of iterative logarithm multiplier - Nandan, Durgesh; Kanungo, Jitendra; Mahajan, Anurag (International Journal of Engineering and Technology, 2018)
Multiplication is one of important arithmetic component for digital signal processing, neural network and image processing. But, it is well known fact that multiplier has most hardware consuming component out of all arithmetic components. Here, it is given a possible solution by using an efficient VLSI architecture of Mitchellâ€™s algorithm based Iterative Logarithmic Multiplier (ILM) with modified architecture of Leading One Detector (LOD) and seamless pipelined technique. The proposed work is based on the hardware minimization at the same error cost than of previously reported architectures. We use VHDL to design the existing and proposed Mitchellâ€™s algorithm based iterative logarithmic multiplier. Both multipliers design are evaluated with the Synopsys design compiler by using 90 nm CMOS technology and compared the results in terms of Data Arrival Time (DAT), area, power, Area Delay Product (ADP) and energy. The proposed Mitchell's based ILM gives 33.18 %, 39.03 % and 31.62 % less ADP, 25.08 %, 38.08 % and 46.72 % less energy for 8, 16, and 32 bits architecture respectively in comparison of the reported ILM. The importance of LODs and seamless pipeline has been shown in an efficient architecture of Mitchell's based ILM.Â